1975
DOI: 10.1029/jc080i012p01650
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic emissions of halides and sulfur compounds to the troposphere and stratosphere

Abstract: Estimates have been made of the annual emissions of HC1, HF, and SO2 to the troposphere and stratosphere from volcanic eruptions. The estimated annual emission rates to the troposphere are 7.5 X 105, 3.8 X 104, and 7.5 X 106 metric tons, respectively, and those to the stratosphere are 2.8 x 104, 1.4 x 10 a, and 2.8 X 105, respectively. The results demonstrate that anthropogenic chlorofluorocarbons have the potential to play a much greater role in stratoSpheric chemistry than the halides from volcanic eruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 22 publications
(16 reference statements)
1
35
0
Order By: Relevance
“…Lidar measurements have shown that the smaller particles are domainant near the top and bottom region of stratospheric aerosol layer (IWASKA, 1980), and same feature is found out also in other observations (BIGG, 1976;HOFMANN and ROSEN, 1977;GRAMS and LABY, 1978;FARLOW et al, 1979). The evaporation rate of H2SO4 estimated here on the basis of laser radar measurements cannot be neglected in the stratosphere in comparison with the production rate of sulfur compounds (5O2, COS, H2S, and so on) due to the transport into the stratosphere across the tropopause as suggested from numerical model calculations (LAZRUS and GANDRUD, 1974;HARRISON and LARSON, 1974;CRUTZEN, 1976) or from the analysis on stratospheric aerosol content, volcanic activity and so on (KELLOGG et al, 1972;JUNGE, 1974;LADLE, 1975).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Lidar measurements have shown that the smaller particles are domainant near the top and bottom region of stratospheric aerosol layer (IWASKA, 1980), and same feature is found out also in other observations (BIGG, 1976;HOFMANN and ROSEN, 1977;GRAMS and LABY, 1978;FARLOW et al, 1979). The evaporation rate of H2SO4 estimated here on the basis of laser radar measurements cannot be neglected in the stratosphere in comparison with the production rate of sulfur compounds (5O2, COS, H2S, and so on) due to the transport into the stratosphere across the tropopause as suggested from numerical model calculations (LAZRUS and GANDRUD, 1974;HARRISON and LARSON, 1974;CRUTZEN, 1976) or from the analysis on stratospheric aerosol content, volcanic activity and so on (KELLOGG et al, 1972;JUNGE, 1974;LADLE, 1975).…”
Section: Introductionsupporting
confidence: 66%
“…In many investigations (KELLOGG et al, 1972;JUNGE, 1974;LAZRUS and GANDRUD, 1974;HARRISON and LARSON, 1974;LADLE, 1975;CRUTZEN, 1976), the role of evaporation process of H2SO4 from sulfate particles in the global circulation of atmospheric sulfur has been left disregarded so far. However this evaporation may be an important secondary source of H2SO4 gas next to the photo-oxidative formation from sulfur compounds originated in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadle (1975) 7.5 SO 2 emission budget deduced from the volume of erupted lava and assuming that SO 2 constitutes 2.5 % of the erupted gas.…”
Section: Methodsmentioning
confidence: 99%
“…However, the source of the stratospheric HCl has not been identified on a firm basis: HCl could be transported from the troposphere by the convective-diffusive transport, or directly by incursion of volcanic gases including a substantial amount of HCl(see Cadle, 1975;Cicerone, 1975;Ryan and Mukherjee, 1975).…”
Section: Introductionmentioning
confidence: 99%